Analysis of The Impact of Fiscal Decentralization on Economic Growth in Indonesia - Suprianik, Suprianik (Fakultas Syariah INSURI Ponorogo, 2023)
This study aims to examine the effect of fiscal decentralization on economic growth in Indonesia. The research sample is journals that discuss the effect of fiscal decentralization on Indonesia's economic growth. The data were then analyzed using the Compare method. The results indicated that, first, fiscal decentralization had a positive and significant effect on economic growth. Second, fiscal decentralization has a negative and significant effect on economic growth. Third, there are many aspects that influence the results of fiscal decentralization in every region in Indonesia.